DNA Repair An Update - Mognato, Maddalena (IntechOpen, 2019)
This book offers a collection of chapters addressing different studies on DNA repair from a cellular and molecular point of view. The various contributions highlight the vastness of DNA repair process and the need for a deeper understanding. To this end, the recent considerations here presented can be a cue for scientists and students working on, or interested in, the subject of DNA repair in human cells. This book may suggest to readers new avenues of interplay between different kinds of DNA damage and cellular response for maintaining nuclear and mitochondrial genomic stability.